Information Science: Science about Information, Misinformation and Disinformation - Tuđman, Miroslav; Mikelić, Nives (2003)
Participants in interaction, particularly in interactive network media (WWW), aim to change intentions, goals, decisions and actions of other participants in communication using information as well as disinfor-mation. Criteria for differentiation among information, misinformation and disinformation are suggested based on the value of information for different participants in interaction. Therefore, the notion of rele-vance needs to be redefined and efficiency of information is analyzed from the point of view of partici-pants in the communication process. Usability of information is defined as a measure of efficiency of the information process judged by the user, while usefulness of information is a measure of sender's effi-ciency regarding the decision-making processes and actions of the information user. Usefulness is a measure of the actual effect of the author (source) of information on the choice of goals, decisions and actions of the information user.
Projekt MZOS
ENG